Konstrukcja wizerunku Makryny w pismach Grzegorza z Nyssy na tle literackiej tradcyji przedstawiania heroicznej kobiety - Szada, Marta (Vox Patrum, 2013)
In the following article I try to investigate how the literary means used by Gregory of Nyssa in his works, especially the Life of St. Macrina, the Dialogue about Soul and Resurrection and the Letter 19. are related to the tradition of depicting heroic woman. In the first part of this paper I consider biblical and martyrological literature, ancient novels, dramas and moralistic works of Plutarch. In the second part I gain a closer look into relations between the creation of Macrina and other hagiographical works of the same time. My purposes are complex. Firstly, I would like to determine the main differences of male and female hero’s narrations. Secondly, I try to examine how Gregory uses conventions and if he is innovative.